Mid-Term Results of EVAR in Severe Proximal Aneurysm Neck Angulation. Issue 1 (January 2015) - Oliveira, N.F.G.; Bastos Gonçalves, F.M.; de Vries, J.-P.P.M.; Ultee, K.H.J.; Werson, D.A.B.; Hoeks, S.E.; Moll, F.; van Herwaarden, J.A.; Verhagen, H.J.M.
Abstract : Objective: To determine if mid-term outcome following endovascular aneurysm repair (EVAR) with the Endurant Stent Graft (Medtronic, Santa Rosa, CA, USA) is influenced by severe proximal neck angulation. Methods: A retrospective case–control study was performed using data from a prospective multicenter database. All measurements were obtained using dedicated reconstruction software and center-lumen line reconstruction. Patients with neck length >15 mm, infrarenal angle (β) >75°, and/or suprarenal angle (α) >60°, or neck length >10 mm with β >60°, and/or α >45° were compared with a matched control group. Primary endpoint was primary clinical success. Secondary endpoints were freedom from rupture, type 1A endoleak, stent fractures, freedom from neck-related reinterventions, and aneurysm-related adverse events. Morphological neck variation over time was also assessed. Results: Forty-five patients were included in the study group and were compared with a matched control group with 65 patients. Median follow-up time was 49.5 months (range 30.5–58.4). The 4-year primary clinical success estimates were 83% and 80% for the angulated and nonangulated groups ( p = .42). Proximal neck angulation did not affect primary clinical success in a multivariate model (hazard ratio 1.56, 95% confidence interval 0.55–4.41). Groups did not differ significantly in regard to freedom from rupture ( p = .79), freedom from type 1A endoleak ( p = .79), freedom from neck-related adverse events ( p = .68), and neck-related reinterventions ( p = .68). Neck angle reduction was more pronounced in patients with severe proximal neck angulation (mean Δα −15.6°, mean Δβ −30.6°) than in the control group (mean Δα −0.39°, mean Δβ −5.9°) ( p < .001). Conclusion: Mid-term outcomes following EVAR with the Endurant Stent Graft were not influenced by severe proximal neck angulation in our population. Despite the conformability of the device, moderate aortic neck remodeling was identified in the group of patients with angulated neck anatomy on the first computed tomography scan after implantation with no important further remodeling afterwards. No device integrity failures were encountered.